Photolabile linkers for solid-phase synthesis - Mikkelsen, Remi J. T. (2020)
Photolabile linkers are the subjects of intense research because they allow the release of the target molecule simply by irradiation. Photochemical release of synthesis products is often facilitated without additional reagents under mild reaction conditions, which may even be environmentally friendly and appealing in the context of greener chemistry. The mild conditions also allow for applications of released material in subsequent biological screening experiments, where contamination with cleavage reagents would be detrimental. This Review pays attention to the increasing number of photolabile linkers developed for solid-phase synthesis and release and covers: (i) o-nitrobenzyloxy linkers, (ii) o-nitrobenzylamino linkers, (iii) α-substituted o-nitrobenzyl linkers, (iv) o-nitroveratryl linkers, (v) phenacyl linkers, (vi) p-alkoxyphenacyl linkers, (vii) benzoin linkers, (viii) pivaloyl linkers, and (ix) other photolabile linkers.